Multipurpose fodder trees in Ethiopia: farmer's perception, constraints to adoption and effects of long-term supplementation on sheep performance. - Kassa, A.M. (Wageningen University & Research, 2008)
Many organizations in Ethiopia have promoted exotic multipurpose fodder tree species particularly Sesbania sesban for livestock feed and soil improvement. Despite the apparent benefits, the number of farmers planting these trees was low. Moreover, some farmers feeding S. sesban reported reproduction problems in sheep. The latter was supported by a few short term reproduction studies conducted in Ethiopia. The study described in this thesis was conducted to assess farmers' perceptions about multipurpose fodder trees and about constraints to adoption, and to study the effects of long-term feeding of S. sesban on sheep performance. The farmers' perception was studied by conducting a field survey among 235 farm households from three districts with different dominant farming systems (wheat, teff [Eragrostis tef] or coffee as the major crop) and the sheep performance studies were a series of experiments at the International Livestock Research Centre in Debre Zeit, Ethiopia. Farmers planted exotic multipurpose fodder trees for their feed value. The valuation for other purposes (soil and water conservation or use as fuelwood) depended on the cropping system, vegetation cover and availability of alternative local fodder trees. The major constraints to adoption were agronomic problems, low multipurpose value, and land shortage. The farmers' decision making criteria to adopt multipurpose fodder trees encompassed multiple objectives: the farmers preferred local fodder trees to exotics for biomass production, multi-functionality, life span, and compatibility to the cropping system. In terms of feed value, ease of propagation and growth potential of local fodder trees were ranked lower than or comparable to exotics. A significant correlation was observed between farmers' feed value score of a fodder tree species and the crude protein content assessed in the laboratory. The number of S. sesban trees currently planted on-farm was ~30% of the recommended number for meat or milk production. Despite some farmers (11.8% of users) reported reproduction problems in sheep, the feed value of S. sesban was appreciated across farming systems. However, the feed value was appreciated more in the wheat- and the teff-based farming systems than in the coffee-based farming system. From the results of the series of on-station experiments conducted for one whole reproductive cycle from post-weaning up to the end of the first lactation, it was observed that supplementation of S. sesban at 30% of the ration (0.98% of body weight) improved the basal and total feed intake and digestibility, growth rate and overall reproductive performance of the sheep. No observable adverse effects of possible anti-nutritional factors in S. sesban were found in this long term study. We conclude that the introduction of exotic multipurpose fodder trees need consideration of farmers' multiple criteria of local resources and knowledge and of the diversity of the farming systems. The introduction should be accompanied by practical training of farmers and of extension agents. The results show that S. sesban is a potential protein supplement that can be used to support the security of livestock or substitute commercial concentrates for smallholder farmers in the Ethiopian highlands.